Identifying Strategies For Universal Coverage Of Immunization - Garg S.K; Mishra V.N; Chopra H; Singh R.B; Bhatnagar M; Garg Amita; Singh J.V; Srivastava R.B (Wolters Kluwer Medknow Publications, 1988)
Various strategies for immunization of children were simultaneously tried in different populations of Meerut City to evolve a suitable strategy for universal coverage of immunization with or without the involvement of permanently posted health workers. The study revealed that immunization can not be effective without the involvement of regular health workers. They are the main force for follow up to ensure complete coverage of schedule of immunization so as to prevent dropouts from immunization drive.